Data Protection Issues in Higher Education with Technological Advancements - Nigel McKelvey (Institute of Advanced Engineering and Science, 2014)
Adhering to laws whilst working or studying in an educational establishment is often fraught with challenges. The Irish Data Protection Act 1988 (Amendment 2003) strives to protect the individual where their personal data is potentially being abused. The advancements in technologies have facilitated educational establishments by improving efficiencies and reducing costs. However, this paper will outline the salient features of the said Act and evaluate how well the law adapts with technologies such as cloud computing and biometrics. It will endeavour to align the law with these technologies and offer a critique of areas that are potentially lacking. Cases will be discussed where precedents have been set by the Irish Data Protection Commissioner and as a result, suggestions for a data protection policy for Higher Education will be proposed. Conclusions will draw upon research conducted and suggest whether the law, as it stands, it suitable with the technologies mentioned.DOI: http://dx.doi.org/10.11591/ijere.v3i3.6140